Dengeki Daisy. Vol. 14 - Motomi, Kyousuke (Shojo beat manga., 2014)
Teru and Kurosaki finally get ahold of "M's Last Testament," and they discover the truth behind their nemesis Akira's past! While Teru opposes helping Akira with his current predicament, Kurosaki is forced to investigate further ... with dire consequences for the both of them!